2000
DOI: 10.2134/agronj2000.925895x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Maturity in Wheat Based on Kernel Water and Dry Matter

Abstract: desiccants or windrowing) without reducing wheat yield, thereby providing better returns in double-crop systems. Estimation of the time of physiological maturity could be beneficialThe most precise method of determining the time of to avoid yield penalties due to lodging, sprouting, hail, and other harvest risks. The aim of our study was to evaluate a simple empirical physiological maturity in crops is to follow kernel dry relationship (model) to determine physiological maturity by simulta-matter accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 23 publications
11
38
0
1
Order By: Relevance
“…The fact that barley reached PM at higher M C than wheat is relevant in the context of this study as it implies that barley may be sprayed with a desiccant herbicide earlier than wheat, further enlarging the difference between both cereals in field release for sowing soybeans. The M C PM found in the present study for wheat does match pretty well previous reported values (Calderini et al, 2000;Pepler et al, 2006). On the other hand, in the case of barley the results of the present study (48%) differed from those reported by Bingham et al (2007b) (40%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The fact that barley reached PM at higher M C than wheat is relevant in the context of this study as it implies that barley may be sprayed with a desiccant herbicide earlier than wheat, further enlarging the difference between both cereals in field release for sowing soybeans. The M C PM found in the present study for wheat does match pretty well previous reported values (Calderini et al, 2000;Pepler et al, 2006). On the other hand, in the case of barley the results of the present study (48%) differed from those reported by Bingham et al (2007b) (40%).…”
Section: Discussionsupporting
confidence: 80%
“…We found barley to have significantly higher MWC and M C PM than wheat. The difference in MWC may well explain the commonly reported higher potential grain weight of barley respect to wheat (Dreccer et al, 1997;Abeledo et al, 2002Abeledo et al, , 2003Calderini et al, 2000;Ehdaie et al, 2008). The fact that barley reached PM at higher M C than wheat is relevant in the context of this study as it implies that barley may be sprayed with a desiccant herbicide earlier than wheat, further enlarging the difference between both cereals in field release for sowing soybeans.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Seed moisture content of winter oilseed rape cultivars at mass maturity stage was high (41-50%), similar to that reported for wheat (37-39%) (Schnyder and Baum, 1992;Calderini et al, 2000), maize (35-36%) Borras and Westgate, 2006), soybean (60%) (Fraser et al, 1982) and sunflower (38%) (Rondanini et al, 2007). However, maximum seed quality of winter oilseed rape cultivars was obtained 10 to 22 days after mass maturity, depending on cultivar and quality test (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Given that grain water content has been found to be a key trait in determining wheat grain weight (Egli, 1990;Saini and Westgate, 2000;Pepler et al, 2006, Hasan et al, 2011, and considering the close balance between water and DM in growing grains (Schnyder and Baum, 1992;Calderini et al, 2000;Saini and Westgate, 2000;Pepler et al, 2006), studying grain water content in response to the source-sink reduction during grain filling could provide useful information on grain growth and its responsiveness to source constraints of wheat as has been shown in maize (Borrás et al, 2003;Borrás and Westgate, 2006).…”
Section: Introductionmentioning
confidence: 99%